Pre-surgical orthopedics success in patients with cleft lip and cleft palate: scoping review - Cristhian Ariel Cisneros Hidalgo; Cristhian Camilo Riveros Carvajal; Karla Xilena Calderon Guzman; kimberly Yulieth Hurtado Cristancho; Claudia Liliana Cabrera Arango (Asociación Latinoamericana de Odontopediatría, 2022)
Background Information: Kerr McNeil, a Scottish prosthetic introduced the Neonatal maxillary orthopedics two centuries ago setting the concept of using orthopedic parts to produced a more natural-like maxilla. Three different types of pre-surgical orthopedics have been described. These are: active, semi-active and passive. Objective: Perform a research in indexed data regarding the success of pre-surgical orthopedics treatment in patients with a condition of cleft lip and cleft palate. Methodology: A computer based research was performed at electronic data bases such as: PUBMED, SCIENCEDIRECT, PROQUEST, COCHRANE, OVIDSP SCOPUS, and MEDLINE. The Booleans researches used in the multiples data bases were OR, AND, NOT. Findings: Thirteen papers met the eligibility standards and were included in this review. Four of them are descriptive, longitudinal and prospective observational studies. Five are clinic reports, one is a retrospective study, one is a Cochrane review, and two are clinic cases and check ups. The orthopedics treatment implementation depended on the kind of extension cases and severity of the cleft palate. Conclusion: the pre-surgical orthopedics is successful if it is implemented at birth up to three months of age. It assures satisfactory results decreasing considerably cleft palate, nasal malformation, and cleft lip before performing Cheilorrhaphy and Palatorrhaphy procedures.